The Small Estates (Distribution) (Amendment) Act 1977 And The Probate And Administration (Amendment) Act 1977 - Balan, P. (Journal of Malaysian and Comparative Law, 1977)
The Small Estates (Distribution) (Amendment) Act 1977 And The Probate And Administration (Amendment) Act 1977